A platform approach to experiential learning - Sandra Robinson (Netcom)
This paper reports on the curriculum design and delivery of a practice-based, experiential learning course, which introduces students in an undergraduate communication and media studies program at a Canadian university to the challenges of working with social data using an analytics platform. The curricular development approach is modeled in part on pedagogical approaches to experiential learning, educational technology and teaching, and also reflects on recent theorizing in platform studies within communication and media studies. The paper argues that by emphasizing a clear link between theory, information ethics, and practice, students can build critical analysis skills necessary to understand the complex relationship between social data and communication and develop data literacy skills that extend their training in critical communication studies.